Penggunaan Media Digital Quizizz berbasis Integrated Joyful Learning dalam Memberdayakan Kreativitas Guru di SD Negeri 1 Sarwogadung sebagai Bentuk Adaptasi Paradigma Merdeka Belajar - Muhafid, Ervian Arif; Hidayat, Wirda Fitriyani; Rahayu, Bekti; Cahyani, Anggilia Dwi; Nugroho, Titis Prasetyo (Prima Abdika: Jurnal Pengabdian Masyarakat, 2023)
The development of the technological era provides new space to be occupied, especially in the field of education. Utilization of digital media makes the process of assessing student learning more effective in obtaining information on learning outcomes. As a teacher, of course the level of creativity is very important to be honed for the better. This article aims to provide an effective teaching and learning experience assisted by digital learning media to increase the creativity of teachers at SD Negeri 1 Sarwogadung. This study uses a qualitative descriptive method to describe the extent of the teacher's understanding and ability to use the Quizizz application. Data collection techniques through observation and interviews. This training has had a significant impact on teachers in increasing their understanding and ability to use the Quizizz application as a variation of learning in the digital technology era.